Analisa Minat Nasabah PT. BPR Chandra Muktiartha dengan Strategi Marketing Mix - Tobit Lala Sadodolu; Nerys Lourensius; Asih Endah Subandiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the impact of the marketing mix strategy (7Ps) - which includes product, price, place, promotion, people, process, and physical evidence - on customer attraction at PT BPR Chandra Muktiartha. The approach used is quantitative with multiple linear regression analysis techniques through SPSS software version 25. The study involved 100 respondents who are active customers of the bank. The results show that overall, the seven components of the marketing mix have a significant influence on customer interest. Individually, six variables namely product, price, promotion, people, process, and physical evidence proved significant, while the place variable did not have a significant impact. The coefficient of determination of 0.610 indicates that 61% of the variation in customer interest is explained by the variables in the marketing mix. The findings provide important input for BPR management to design a more optimal marketing strategy to reach and retain customers.